Practical skills in biology - Jones, A. M. (Allan M.), 1945- (Pearson, 2021)
"The primary aim of this revision of Practical Skills in Biology was to update the text, but we also wished to respond to the helpful comments of several anonymous reviewers of the 6th edition, and in so doing, to reorganise the chapters and include significant new material. The main structural changes we have made are to (1) reorder and rewrite several chapters in the first two sections; (2) add three new chapters on working with bacteria, eukaryotic microbes and viruses; (3) include a new chapter on assaying biomolecules; and (4) revise the material on use of software and online sources in biology, to reflect the greater level of knowledge and experience of today's students. In terms of the text itself, we have sought to use more positive phrasing throughout, to emphasise the active nature of learning in this discipline. Some details of further changes and additions are listed on the back cover. The text references and sources for further study have been updated, while the popular study exercises have been retained. We thank again everyone who helped us with earlier editions, and for this one acknowledge in particular the assistance of Jill Muller of CQUniversity in helping to revise the material on finding and citing sources, Lou Attwood for her work in copy editing the text, and Indrasena Mukhopadhyay and Nikhil Kumar in coordinating the production of the text and images, together with other staff who were involved in the book's production. We also recognise Rufus Curnow for his enduring support of all of the Practical Skills titles. Although this revision has largely been the work of two of the original authors ( JDBW and RHR), we thank Allan Jones and Dave Holmes for their contributions to the Practical Skills series throughout the years. Finally, we thank staff at all institutions who have adopted this text. The practical syllabus in biology has come under increasing pressure in recent years, with diminishing resources and timetabling allocation. Yet such changes cannot alter the fundamental fact that biology, in all its facets, is primarily a practical subject - one in which students learn most effectively through 'hands-on' experience in the lab and the field. We hope that this book will help students to prepare better for practicals, projects, lectures, seminars, examinations and assignments, to gain greater enjoyment from taking part in them and to learn more about the organisms that populate our world and the ecosystems that support them. The book is divided into several sections: - Chapters 1-8 cover general skills, including selfmanagement and personal development; how to learn; teamwork; and how to locate, evaluate and cite sources. - Chapters 9-18 deal with assessment, including written assignments; practicals and projects; oral and poster presentations; revision and examinations. - Chapters 19-73 cover a broad range of specific practical skills and techniques, ranging from basic laboratory procedures to more advanced techniques. - Chapters 74-80 explain data analysis and presentation, ranging from the presentation of results as graphs or tables through to the application of statistical tests, with worked examples. - Study exercises and problems are provided for each chapter. They enable you to check your understanding and to practice key calculations, either on your own, under the guidance of a tutor, or working with other students.